Posterior Reversible Encephalopathy Syndrome After Azathioprine Administration in Severe Ulcerative Colitis. Issue 1 (29th January 2021) - Vernia, Filippo; Di Ruscio, Mirko; Massella, Arianna; Variola, Angela; Montanari, Renzo; Bocus, Paolo
ABSTRACT: Posterior reversible encephalopathy syndrome is a rare syndrome characterized by brain edema and neurological symptoms, often resulting from several drugs. Treatment is based on discontinuation, and diagnosis is thus essential. Only 13 cases of posterior reversible encephalopathy syndrome have been reported in inflammatory bowel diseases, and we present the first after azathioprine in adults. A 56-year-old patient with active ulcerative colitis was found unconscious 5 days after the institution of azathioprine. Right-sided hemiplegia was found after the patient regained consciousness. Magnetic resonance imaging showed altered signal associated with diffusion restriction in the occipital lobe and cerebral vasogenic edema. Complete regression of neurological signs occurred after azathioprine discontinuation.